Entrepreneur Attributes and Formalization of Micro, Small and Medium Enterprises in Tanzania. Issue 4 (2nd October 2018) - Ishengoma, Esther K.
ABSTRACT: New institutional economics literature underscores the role of entrepreneur attributes in structuring the entrepreneur's views and decision-making about (in)formalizing the business while considering the environment which shapes one's perceptions. However, empirical knowledge on same, based on the African/Tanzanian context, remains scant. Based on Tanzanian national survey data from 5549 micro, small and medium enterprises, this paper assesses the influence of entrepreneur attributes on business formalization while controlling for structural and institutional factors. The results reveal that attributes likely to increase the probability of formalizing one's business include being either a male, aged between 31 and 50, opportunity-driven or having at least secondary education.